ANALISIS PENGARUH CITRA MEREK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK KFC PADA MAHASISWA UNPRI MEDAN - Elaine Kang; Kevin; Mohd. Nawi Purba; Ara Auza (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Kentucky Fried Chicken is a very famous fast food restaurant or commonly called KFC. The purpose of this study is to determine and analyze the influence of Brand Image, Price and Promotion on KFC Product Purchasing Decisions on Unpri Medan Students. This research approach is based on a quantitative approach. The research sample was 97 respondents using Simple random sampling as a sampling technique. The partial test results obtained a value of t count> t table (3.816> 1.986) and a significance of 0.000 <0.05, meaning that H1 is accepted, namely Brand Image influences KFC Product Purchasing Decisions on Unpri Medan Students. The partial test results obtained a value of t count> t table (2.992> 1.986) and a significance of 0.004 <0.05, meaning that H2 is accepted, namely Price influences KFC Product Purchasing Decisions on Unpri Medan Students. The partial test results obtained a calculated t value > t table (2.750 > 1.986) and a significance value of 0.007 < 0.05, meaning that H3 is accepted, namely that Promotion influences the Decision to Purchase KFC Products on Unpri Medan Students. The simultaneous test results obtained a calculated F value (29.946) > F table (2.70) and a significance probability of 0.000 < 0.05, meaning that H4 is accepted. Brand Image, Price and Promotion influence the Decision to Purchase KFC Products on Unpri Medan Students.